2014
DOI: 10.1177/0956462414545796
|View full text |Cite
|
Sign up to set email alerts
|

Components of resilience in gender: a comparative analysis of HIV outcomes in Kenya

Abstract: Gender is a critical concept of human immunodeficiency virus (HIV) sexual risk; yet, few studies have examined the intersection between risk and protective factors associated with incidence of HIV among couples. The paper examines gender-specific constructs of resiliency among couples in Kenya. Using data from the Demographic and Health Surveys, Kenya (2008/2009), we apply logistic regression techniques to analyse three resilience-related outcomes (condom use, HIV test and knowing an HIV test place) in estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…A stratified analysis showed that there was a significant association between IPV and consent to test for HIV in rural areas but not in urban areas. However, in the multivariable analysis, there was no significant relationship between IPV and consent to test for HIV.Satyanarayana (2009) [29]IndiaWomen (18–50 years)100Cross-sectionalThis study found no significant differences between women who consented to test for HIV and those who did not in terms of their exposure to violence.Pearlman (2005) [30]U.S.Pregnant and post-partum women (≤ 3 months after delivery) enrolled in in a federally funded nutrition program for women, infants and children (WIC)433Cross-sectionalExperiencing IPV in the past 12 months was associated with reduced probability of receiving a prenatal HIV test.Tucker (2003) [31]U.S.Women (18–55 years) sheltered and low-income housed898Cross-sectionalWomen who had ever experienced sexual violence since they were 18 were significantly more likely to have ever tested for HIV.Nikolova et al (2015) [32]KenyaHeterosexual couples (men and women N = 2862)1431Cross-sectionalExperiences of sexual violence were not significantly associated with ever having tested for HIV among women.Mohammed et al (2017) [33]EthiopiaHeterosexual couples (men and women N = 420)210Cross-sectionalWomen who reported ever experiencing physical violence from their partner were significantly less likely to have tested for HIV.Etudo et al (2016) [34]U.S.HIV-negative adult women (≥18 years)79Cross-sectionalWomen who experienced emotional, physical, and/or sexual violence were less likely to test for HIV in the past year, report a longer time since their last HIV test, and reported more barriers to HIV testing, compared to women who had not experienced violence.Rountree et al (2016) [35]U.S.Adult women (≥18 years)18,917Cross-sectionalWomen who experienced IPV in their lifetime reported higher rates of HIV testing compared to women who had never experienced IPV.Nasrullah et al (2013) [36]U.S.Non-pregnant adult women (≥18 years)29,209Cross-sectionalWomen who experienced threatened violence, attempted violence, or unwanted/forced sex were significantly more likely to have ever been tested for HIV compared to women with no IPV history. However, nearly half of the women who experienced IPV had never tested for HIV.Brown et al (2013) [37]U.S.Adult women (≥18 years)30,182Cross-sectionalSurvivors...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A stratified analysis showed that there was a significant association between IPV and consent to test for HIV in rural areas but not in urban areas. However, in the multivariable analysis, there was no significant relationship between IPV and consent to test for HIV.Satyanarayana (2009) [29]IndiaWomen (18–50 years)100Cross-sectionalThis study found no significant differences between women who consented to test for HIV and those who did not in terms of their exposure to violence.Pearlman (2005) [30]U.S.Pregnant and post-partum women (≤ 3 months after delivery) enrolled in in a federally funded nutrition program for women, infants and children (WIC)433Cross-sectionalExperiencing IPV in the past 12 months was associated with reduced probability of receiving a prenatal HIV test.Tucker (2003) [31]U.S.Women (18–55 years) sheltered and low-income housed898Cross-sectionalWomen who had ever experienced sexual violence since they were 18 were significantly more likely to have ever tested for HIV.Nikolova et al (2015) [32]KenyaHeterosexual couples (men and women N = 2862)1431Cross-sectionalExperiences of sexual violence were not significantly associated with ever having tested for HIV among women.Mohammed et al (2017) [33]EthiopiaHeterosexual couples (men and women N = 420)210Cross-sectionalWomen who reported ever experiencing physical violence from their partner were significantly less likely to have tested for HIV.Etudo et al (2016) [34]U.S.HIV-negative adult women (≥18 years)79Cross-sectionalWomen who experienced emotional, physical, and/or sexual violence were less likely to test for HIV in the past year, report a longer time since their last HIV test, and reported more barriers to HIV testing, compared to women who had not experienced violence.Rountree et al (2016) [35]U.S.Adult women (≥18 years)18,917Cross-sectionalWomen who experienced IPV in their lifetime reported higher rates of HIV testing compared to women who had never experienced IPV.Nasrullah et al (2013) [36]U.S.Non-pregnant adult women (≥18 years)29,209Cross-sectionalWomen who experienced threatened violence, attempted violence, or unwanted/forced sex were significantly more likely to have ever been tested for HIV compared to women with no IPV history. However, nearly half of the women who experienced IPV had never tested for HIV.Brown et al (2013) [37]U.S.Adult women (≥18 years)30,182Cross-sectionalSurvivors...…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies found no significant relationship between experiences of violence and uptake of HIV testing among women [28, 29, 32, 41, 42, 44, 62]. Two of these studies utilized longitudinal designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have linked gender-based inequalities and disparities in women's health to poor health outcomes that involve marital rape and HIV risk (e.g., Francisco et al, 2013;Gibbs et al, 2015;Nikolova, Small, & Mengo, 2015;Winchester, 2016). For example, an association was found with regard to the influence of gender inequality on HIV risk and domestic violence among African American, Hispanic, and Tanzanian women (Karamagi, Tumwine, Tylleskar, & Heggenhougen, 2006;Nyamhanga & Frumence, 2014;Raj, Silverman, & Amaro, 2004;Wingood & DiClemente, 2000).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Furthermore, perceived risk of acquiring or transmitting HIV is associated with changes in the frequency of both risky sexual practices (Ostrow et al, 2002) and precautionary behaviors (Gerrard, Gibbons, & Bushman, 1996). Serodiscordant couples in Kenya often display low levels of agreement in their perception of shared risk factors for HIV infection (Nikolova, Small, & Mengo, 2014). Heteronormative gender roles likely influence HIV risk behavior and the uptake, use, and adherence to novel HIV prevention methods such as PrEP and do so differentially across genders.…”
Section: Introductionmentioning
confidence: 99%